MODEL KEPEMIMPINAN CARE GROUP DALAM PENDIDIKAN HOLISTIS [A LEADERSHIP MODEL OF CARE GROUPS IN HOLISTIC EDUCATION] - Nico Tanles Tjhin; Dylmoon Hidayat (Polyglot, 2019)
A study program at a private higher education institution, namely CT, a transformational holistic education organization, implements an academic and non-academic guidance program through small groups called CARE Groups (CG). However, regardless of there being a CG program, there are still many cases of CT students breaking rules. These range from general cases to more severe ones that result in warning letters. The discrepancy found in the range of cases is the topic of this study, which focuses on the perspective of the CG leadership. The qualitative method of case study was utilized so that the data may be accurate and in-depth for analysis, in order for there to be further discussion. The three main findings that answered the problem formulated in this study were the description of strategies and CT efforts in equipping CG Leader (CGL), an explanation of the reasons for the emergence of cases among students, and the formulation of an ideal profile for a CGL.BAHASA INDONESIA ABSTRAK: Sebuah program studi di suatu perguruan tinggi swasta, sebut saja CT, suatu lembaga pendidikan holistis yang transformasional menerapkan suatu program bimbingan akademik dan non-akademik berbentuk kelompok kecil bernama CARE Group (CG). Namun, terlepas dari adanya instrumen CG, kasus pelanggaran peraturan di kalangan mahasiswa CT kerap kali muncul, mulai dari kasus umum sampai kasus berat yang memiliki konsekuensi Surat Peringatan (SP). Kesenjangan tersebut menjadi topik pembahasan dalam studi ini, berfokus pada segi pandangan kepemimpinan CG. Metode penelitian kualitatif studi kasus digunakan agar mendapatkan data yang akurat dan mendalam untuk dianalisis dan dibahas lebih lanjut. Diperoleh tiga temuan utama yang menjawab rumusan masalah dari penelitian ini, yaitu deskripsi strategi dan upaya CT dalam memperlengkapi CG Leader (CGL), penjelasan akan alasan masih munculnya kasus di kalangan mahasiswa, dan rumusan sebuah profil ideal bagi seorang CGL.